“If you can’t see a dilemma in this situation you should probably regard it as a warning”: a metasynthesis and theoretical modeling of general practitioners' opioid prescription experiences in primary care - Kennedy, Mary-Claire; Pallotti, Phoebe; Dickinson, Rebecca; Harley, Clare (SAGE, 2018)
Background: The prescribing of opioids has increased internationally in developed countries in recent decades within primary and secondary care.1 The majority of patients with chronic non-malignant pain (CNMP) are managed by their GP.2 Recent qualitative studies have examined the issue of opioid prescribing for chronic non-malignant pain (CNMP) from a GP viewpoint. Several factors have been reported to influence the prescribing of opioids for CNMP including aetiology of pain condition, co-morbidities, access to specialised care, history of drug abuse and professional scrutiny. We require a better understanding of problems GP’s face when making opioid prescribing decisions, and interventions to provide better supports in the prescribing of opioids for CNMP.The aim of this study is to identify and synthesize the qualitative literature describing the factors influencing the nature and extent of opioid prescribing in CNMP in primary care. A theoretical model is then proposed which seeks to explain the relationship between factors influencing prescribing of opioids for CNMP by GPs. Methods: MEDLINE, Embase, PsychINFO, Cochrane Database, International Pharmaceutical Abstracts, Database of Abstracts of Reviews of Effects, CINAHL and Web of Science were systematically searched from January 1986-Feb 2018. Studies that documented GP’s experiences and behaviours relating to prescribing opioids for chronic non-alignant pain in a primary care setting were included. Studies were excluded if they were non-English language, theoretical or methodological articles, policy documents, conference abstracts or presentations, or where quotations were not clearly attributed to GPs participating in the study.The reviewers then independently assessed the full text of the articles using the Critical Appraisal Skills Programme (CASP) tool for qualitative research. The papers were coded by two researcher and these codes organised using Thematic Network Analysis. Basis themes were defined initially, organising themes were then developed followed by global themes which summarised the key theories emerging from the articles. Finally, a theoretical model was derived by the researchers using the global themes to explain the interplay between factors influencing opioid prescribing decisions. Results: From 7020 records, 18 full text papers were assessed, and 13 studies included in the synthesis; 9 were from USA, 3 from UK and 1 from Sweden. Seven organising themes were identified including trust and mistrust, the importance of aetiology, monitoring of prescription use, physical, psychological and societal harm, consultation variables, inadequate pain management, stigma and stereotypes and system barriers to effective and safe prescribing such as limited access to specialist care or support from allied healthcare professionals in primary care. Four global themes emerged and included suspicion, risk, agreement and encompassing systems level factors. These global themes are inter-related and capture the complex decision-making processes underlying opioid prescribing whereby the physician both consciously and subconsciously quantifies the risk-benefit relationship associated with initiating or continuing an opioid prescription. Conclusion: Prescribing of opioids for CNMP is influenced by a myriad of factors. Rather, than a simple risk-benefit view of the process, it is more useful to view this as a dynamic process in which unique considerations such as the morality of opioid use exert an effect. Recognising the inherent complexity of the process and the limitations of healthcare systems, guidelines directed at GPs should offer more nuanced recommendations on managing opioid prescribing consultations in primary care.